2019
DOI: 10.1016/j.btre.2019.e00335
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory effects of leaf extract of Lawsonia inermis on Curvularia lunata and characterization of novel inhibitory compounds by GC–MS analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…Microorganism synthesized an iron-chelating, low molecular weight compound known as siderophore [161] that checks the pathogenic microorganism's growth by preventing the availability of iron by binding to the freely available form of iron (Fe 2+ ) in the rhizosphere [159]. PGPR produce siderophores to competitively acquire ferric ions under the iron-limiting conditions [162][163][164]. However, de Villegas et al [165] reported that increased iron concentration in the environment has a negative effect on the siderophore production.…”
Section: Hcn/siderophore/iaa Productionmentioning
confidence: 99%
“…Microorganism synthesized an iron-chelating, low molecular weight compound known as siderophore [161] that checks the pathogenic microorganism's growth by preventing the availability of iron by binding to the freely available form of iron (Fe 2+ ) in the rhizosphere [159]. PGPR produce siderophores to competitively acquire ferric ions under the iron-limiting conditions [162][163][164]. However, de Villegas et al [165] reported that increased iron concentration in the environment has a negative effect on the siderophore production.…”
Section: Hcn/siderophore/iaa Productionmentioning
confidence: 99%
“…Around 300,000 higher plant species cover the earth’s surface, and according to previous reports revealed that each species harbor either one or an abundance of endophytic microflora within them. Out of these plant species that present on the globe, only a few dozen, have been studied so far for their endophytic microbial community [ 8 , 66 ]. Considering this rationale and also the fact that since the flora of the Great Indian Thar Desert is full of ethnopharmacologically important plants have been studied so far for their endophytic community and their biopotential, therefore, endophytic diversity of some medicinally important plants of the Thar Desert will be discussed in this section.…”
Section: Biodiversity Of Endomicrobiome Of Plantsmentioning
confidence: 99%
“…The carrier gas is high purity helium gas [10], 1 ml/min. MS: the mass range detected by the MS program is 30-600 amu, the voltage is 70 ev, the ion source and four stage temperature are set at 230 ℃ and 150 ℃ [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Sample Preparationmentioning
confidence: 99%